SUPPLY CHAIN FEATURES OF THE AEROSPACE INDUSTRY PARTICULAR CASE AIRBUS AND BOEING - Daniela MOCENCO (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
Aerospace sector is one of the most globalized industries in terms of market structure and production system. Through aircraft development programs aviation industry has introduced new solutions to develop its products. The role of the partners involved in the development programs for the new generation aircraft is becoming increasingly important. Supply chain management has become a key factor for major manufacturers in the industry. The new strategies introduced by the aircraft manufacturers have increased the complexity of the supply process, design and production from the aviation industry. This paper highlights a series of factors regarding the aircraft programs supply chain management. In the first part are described the problems encountered by the manufacturers and airlines during the development of the most recent aircraft launched A350XWB and B787 Dreamliner; the second part focuses on the organizational structure of the supply chain, suppliers role within supply chain and also there are described the effects of the new strategies adopted by Airbus and Boeing in the aircraft development; the last part focuses on the risks and challenges that aviation industry is facing.